A review of alcohol pricing and its effects on alcohol consumption and alcohol-related harm - Dhalwani, Nafeesa (Dow University of Health Sciences, 2011)
Alcohol has a complex relationship with any given society. On one hand, it may have some benefits by providing a means of leisure and socialization and a source of revenue through taxation of its sales while on the other hand; it has harmful effects by being a direct cause of many medical illnesses, accidents and crime.1 The number of deaths directly related to alcohol in England in 2008 were 6,769, which is a 24% increase from 2001.2 To combat this rising number of alcohol-related problems, the government has introduced various strategies and indicators in order to monitor the effectiveness of interventions. NI39 is one such national indicator for alcohol-related harm, which measures alcohol-related admissions per 100,000 populations on a quarterly and yearly basis, with the first quarter starting in April and the last quarter ending in March. This rate (NI39) for England in 2009/2010 was 1,743/100,000, which is a 10% increase from 2008/2009 statistics.3 Furthermore, the NI39 estimates for the first two quarters of 2010/11 are about 942/100,000, predicting a 9% further increase from previous year.4 In addition, there was an average of 271 alcohol dependence-related prescriptions in England per 100,000 in 2009, costing the National Health Service about £2.38 million.5 Hence, we can see that the burden of alcohol misuse in England is huge, making it a priority problem in public health.